A confecção de jogo analógico para o ensino da história da cidade de São Borja, RS, para os alunos do 4º ano da Escola Municipal Aparício Mariense - Rodrigues, Marcia Cristina Cabreira (2020)
Teaching History is always a challenge, since this curricular component is always changing and transforming, as it accompanies human actions over time. When this teaching is aimed at children this 9 and 10 years old it is even more challenging, since texts, textbooks are presented, most of the times unattractive to these students. For this reason, a Board Game was made and applied to these children in order to more accurately fix points related to the History of São Borja, content of the teaching stage of the fourth year of Elementary School; more precisely, the fourth year classes of the Aparício Mariense Municipal Elementary School, in the city of São Borja, RS. The game was elaborated from direct observations of the classes, to evaluate their ability to interact in the realization of the same and also through readings and reflections of scientific texts that greatly collaborated in the realization and application of the project and this Master's dissertation.